The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1115/1.3239576
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Layer and Loss Measurements on the Rotor of an Axial-Flow Turbine

Abstract: The aerodynamic efficiency of an axial-flow turbine is significantly less than that predicted by measurements made on equivalent cascades which operate with steady inflow. This difference in efficiencies is strongly dependent upon the rotor-stator axial spacing. An experimental investigation of the rotor-stator interaction has therefore been conducted using a large-scale, low-speed turbine. The blade profile loss and surface shear stresses are presented for the midspan of the rotor and for a rectilinear cascad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…It is possible to calibrate hot films, but this is a difficult and time consuming process see Hodson [15] and Davies and O'Donnell [16]. Also, errors of 20% or more arise when hot films calibrated in a laminar flow are used to measure a turbulent flow.…”
Section: Methodsmentioning
confidence: 98%
“…It is possible to calibrate hot films, but this is a difficult and time consuming process see Hodson [15] and Davies and O'Donnell [16]. Also, errors of 20% or more arise when hot films calibrated in a laminar flow are used to measure a turbulent flow.…”
Section: Methodsmentioning
confidence: 98%
“…Evans (1978) carried out a similar study but, because the effect of wakes was not separated from the three-dimensional flow influence, the results were not conclusive. Work on a turbine rotor by Hodson (1984) had shown the significant impact of wakes on the increase of profile loss compared with that in a no-wake flow. More understanding of the wake interaction with a laminar boundary layer has been gained by the results obtained in the experimental work of Pfeil, et al (1983) on a flat plate and Doorly and Oldfield (1986) on a turbine blade.…”
Section: Introductionmentioning
confidence: 97%
“…A phase-locked data-logging technique was used and 100 samples were used to derive ensemble-averaged quantities; it was found that there was little improvement in using more samples. The data acquisition facilities and the techniques were similar to those used by Hodson (1984) and were described in detail by Dong (1988).…”
Section: Introductionmentioning
confidence: 99%
“…The interactions have been studied using turbomachines 4 and simulations. 5 Much of this research has concluded that the most significant effect is the periodic forcing of the transition of the blade surface boundary layers and the influence this has upon the aerodynamic and thermodynamic performance of the blade row.…”
Section: Introductionmentioning
confidence: 99%